PENGARUH PEMBERIAN DOSIS PUPUK NPK DAN KOSENTRASI URIN SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis Sativus L.) - Muh. Ali Sabbaha; Palupi Puspitorini; Jeka Widiatmanta; Agung Setya Wibowo (grafting, 2023)
This study aims to determine the interaction of NPK fertilizer and cow urine on the growth and yield of cucumber plants. To determine the best dose of NPK fertilizer on the growth and yield of mentimub plants, to determine the dosage of cow urine that is suitable for the growth and yield of cucumber plants. This research was conducted using factorial randomized block design (RBD) with 2 factors, the first factor was the dose of NPK fertilizer (N) consisting of 3 levels, namely 250 kg / ha (N1), 350 kg / ha (N2) 450 kg / ha (N3). The second factor is a cow urine dose of three systemf, namely: 300 ml / plot (U1), 400 ml / plot (U2), 500 ml / plot (U3). The observed variables include leaf area, diameter stem, fruit length, amount of fruit, and fruit weight. Data were analyzed using variance analysis (ANOVA) level of 5% and further testing with Duncan's Multiple Range Test (DMRT). The results showed that: There was no real interaction between NPK doses and cow urine fertilizer on the growth and yield of cucumber plants. The treatment of NPK fertilizer dose of 250 kg / ha (N2) significantly affected the length of the fruit. The best length of fruit yield was 20,7033 cm 2 harvest age 51 HST and the best fruit yield weight was 450 kg / ha amounting to 3367.11 g. in all harvests.